Manajemen Asuhan Keperawatan Kegawat Darurata n Pada Perempuan Dewasa Dengan Diabetes Mellitus Tipe II Dengan Masalah Keperawatan Ketidakstabilan Kadar Glukosa Darah - shanti dafris (Jurnal Ilmiah Cerebral Medika, 2021)
Diabetes Mellitus (DM) is a disease characterized by the occurrence of hyperglycemia anddisturbances of carbohydrate, fat, and protein metabolism associated with absolute or relativedeficiency of insulin action and/or secretion. The purpose of the study was to provide emergencynursing care to patients with diabetes mellitus with the problem of unstable blood glucose levels.The research design used is qualitative. In patients there is instability of blood glucose levels dueto irregular eating patterns and medication, frequent hunger, frequent urination, weight loss(BB), and non-adherence in blood sugar control. Patients are treated with nursing care with thesame intervention and implementation according to the etiology of the problem. Based on theresearch, the results showed that the problem was partially resolved. Therefore, in providingnursing actions to overcome the problem of unstable blood glucose levels, it is recommended tofind out the main causative factors and pay attention to other causal factors. It aims to avoid therecurrence of diabetes mellitus.